Похибки розрахунку статичних характеристик гідродинамічних вимірювальних перетворювачів реологічних параметрів в’язкопластичних рідин - Крих, Г.; Робур, М. (Видавництво Національного університету «Львівська політехніка», 2000)
The theoretical account of static models of hydrodynamic measuring transducers of plastic viscosity and yield shear stress of viscoplastic liquids based on bridge measuring transducers is considered. Their approximate static models are represented. The errors of calculation of rheological parameters on these models on an example of liquid with given ranges of measurement of rheological parameters are determined.